VISUALISASI KONTRAS SPEKEL MENGGUNAKAN PROGRAM SCIKIT IMAGE DAN PULSA DETAK JANTUNG BERBASIS ARDUINO UNO PADA TIKUS PUTIH YANG DIINDUKSIKAN ALOKSAN - Zulkarnain Zulkarnain; Nur Melati (Universitas Riau, 2019)
Speckle contrast visualization and heart rate pulses on rats induced with alloxan were successfully carried out. This research aims to visualize speckle contrast measurements using the Scikitimage program and analyze the relationship between speckle contraston rats to blood sugar levels and also to determine the effect of alloxan induced on heart rate frequency in rats. This study obtained speckle pattern image data from rats induced by alloxan with variations in concentrations of 35%, 55% and without alloxan for 12 days of treatment. The sample used were3 to 5 months old. The method conducted in speckle contrast visualization was using blob detection with Laplacian of Gaussian algorithm to obtain speckle contrast values while the visualization of heart rate pulse based on Arduino Uno was done using the Integrated Development Environment (IDE) program. The results obtained from image processing using the Scikitimage program show that the contrast value could achieved decreasing with increasing blood sugar levels and the results obtained for detection of heart rate was the greater the blood sugar level the greater the heart rate (beat per minute) measured.